Evaluación cefalométrica del complejo malar - Gómez-Jaramillo, Aurora (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The diagnosis of the midface has been based exclusively from the clinical appreciation of the patient, converting its diagnosis in something notably subjetive and difficult that could change between the different clinicians. The cephalometric criteria for the evaluation of the midface has depend principally from the angle SNA(Sella-Nasion-A), which only indicate to us the position of point A in relation to the anterior cranial base. This investigation pretends to stablish some averages, which could be useful as cephalometric evaluation parameters of the malar region and correlationate this findings with the clinical appreciation of the patient. The measurements made, were: angles S.N.O. (Sella-Nasion-Orbitale), NOA (Nasion-Orbitale, Point A) and SNA. The relations SO/SA and the distance perpendicular from 0 (Orbital) to the line NA. The patients were grouped in three according to the SNA value, taking as averages thoes described by Riolo (1), Group 1, were those who had a SNA below the average. Group 2 and average SNA angle and group 3 a SNA above the average. It was found that angle S.N.O. and distance O-NA, were important parameters to evaluate the malar complex and the maxillo-rnalar relation. The maxillary hipoplasia generally is acompanied by a malar hipoplasia. No significative differences were found according to sex. No significative association between the clinical appreciation and the cephalometric evaluation was also found.